Smart City: From Concept To Implementation - Chrisidu-Budnik, Agnieszka; Przedańska, Justyna (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
This article presents four interpretations of the term smart city, which are not competitive with each other, but even so, municipal authorities knowingly choose the so-called strong preference, as well as shows the conditions for implementing Smart City Projects, which is treated as one of the mechanisms of implementing the idea of the smart city. We also draw attention in the article to the logic of preferences, which is rooted in every decision-making process of municipal authorities, which were forced to make constant choices in conditions of conflicting expectations of stakeholders.
Keywords: administration; project; smart